Health Promotion in Children and Adolescents through Sport and Physical Activities-2nd Edition - Bianco, Antonino (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue Book presents a total of 12 papers, encompassing 31 different affiliations, with authors from 12 different countries spanning three different regions of the world (Europe, North America, and Asia).